Self-rated physical and mental health among older adults 80 years and older: cross-sectional results from a National community sample in Thailand - Supa Pengpid; Karl Peltzer (BMC, 2023)
Abstract Background The aim of this study was to assess the self-reported physical health (SRPH) and self-reported mental health (SRMH) of older adults 80 years and older in Thailand. Methods We analyze national cross-sectional data from the Health, Aging and Retirement in Thailand (HART) in 2015. Physical and mental health status was assessed by self-report. Results The sample included 927 participants (excluding 101 proxy interviews), 80-117 years, median age 84 years [interquartile range (IQR) 81-86 years]. The median SRPH was 70.0 (IQR = 50.0-80.0), and median SRMH was 80.0 (IQR = 70.0 to 90.0). The prevalence of (good) SRPH was 53.3%, and the prevalence of (good) SRMH was 59.9%. In the final adjusted model, low or no income, living in the Northeastern, Northern and Southern region, daily activity limitations, moderate/severe pain, having one or two or more physical conditions, and low cognitive functioning were negatively associated, and higher physical activity was positively associated with good SRPH. No or low income, residing in the northern region of the country, daily activity limitations, low cognitive functioning, and probable depression were negatively associated with good SRMH, and physical activity was positively associated with good SRMH. Conclusion SRPH and SRMH was relatively high rated among the oldest old in Thailand, and influenced by various social, economic, and health-related factors. Special attention should be given to those with no or low income, those living in the non-central regions and those having no or low formal social engagement. Health care and other services should improve physical activity, financial support, and physical and mental care management to promote physical and mental well-being of older adults 80 years and older in Thailand.